2016
DOI: 10.2147/ijn.s110796
|View full text |Cite
|
Sign up to set email alerts
|

Polymer nanoparticles for cross-presentation of exogenous antigens and enhanced cytotoxic T-lymphocyte immune response

Abstract: Effective induction of an antigen-specific cytotoxic T lymphocyte (CTL) immune response is one of the key goals of cancer immunotherapy. We report the design and fabrication of polyethylenimine (PEI)-coated polymer nanoparticles (NPs) as efficient antigen-delivery carriers that can induce antigen cross-presentation and a strong CTL response. After synthesis of poly( d , l -lactide- co -glycolide) (PLGA) NPs containing ovalbumin (OVA) by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…As potential vaccine carriers, NPs could enhance antigen cross-presentation of DCs, thereby produce stronger antitumor immunity. For example, as shown in both in vivo and in vitro experiments, treatment with polymer NPs such as γ-PGA NPs ( 114 , 115 ), PLGA NPs ( 116 ), polyethyleneimine NPs ( 117 ) and poly(propylene sulfide) NPs ( 52 ) promoted OVA-mediated cross-presentation in DCs by different mechanisms. Changing size and surface chemistry of NPs were effective ways to regulate their effects on antigen cross-presentation intensity of DCs ( 118 , 119 ).…”
Section: Nps Affect DC Functionsmentioning
confidence: 97%
“…As potential vaccine carriers, NPs could enhance antigen cross-presentation of DCs, thereby produce stronger antitumor immunity. For example, as shown in both in vivo and in vitro experiments, treatment with polymer NPs such as γ-PGA NPs ( 114 , 115 ), PLGA NPs ( 116 ), polyethyleneimine NPs ( 117 ) and poly(propylene sulfide) NPs ( 52 ) promoted OVA-mediated cross-presentation in DCs by different mechanisms. Changing size and surface chemistry of NPs were effective ways to regulate their effects on antigen cross-presentation intensity of DCs ( 118 , 119 ).…”
Section: Nps Affect DC Functionsmentioning
confidence: 97%
“…It has been already demonstrated by other groups, that cross-presentation of exogenous OVA antigens by DCs occurs rapidly, which was determined e.g. between 6 and 16 hours [72][73][74]. The strong decline in H-2Kb-bound SIINFEKL presentation in DC2.4 cells after 24 hours might be explained by the lack of further maturation stimuli (e.g.…”
Section: Discussionmentioning
confidence: 76%
“…We observed proliferation of CD8 + T cells, but the percentages of Ki67 + cells within this CD8 + T cell pool is low due to the fact that the majority of the T cells in the co-culture is still unspecific for the CMVpp65 peptide. Previous studies have demonstrated that nanoparticle-mediated delivery of antigens can dramatically enhance and sustain exogenous antigen presentation by MHC class I [38,39]. In a previous study, we already demonstrated in vitro that encapsulation of poly(I:C) or/and CpG together with an MHC class II restricted model antigen is suitable for the induction of a CD4 + T cell response [20].…”
Section: Discussionmentioning
confidence: 95%